A stochastic multiple players multi-issues bargaining model for the Piave river basin - Alessandra Sgobbi; Carlo Carraro (Center for Economic Studies and ifo Institute (CESifo), 2007)
The objective of this paper is to investigate the usefulness of non-cooperative bargaining theory for the analysis of negotiations on water allocation and management. We explore the impacts of different economic incentives, a stochastic environment and varying individual preferences on players' strategies and equilibrium outcomes through numerical simulations of a multilateral, multiple issues, non-cooperative bargaining model of water allocation in the Piave River Basin, in the North East of Italy. Players negotiate in an alternating-offer manner over the sharing of water resources (quantity and quality). Exogenous uncertainty over the size of the negotiated amount of water is introduced to capture the fact that water availability is not known with certainty to negotiating players. We construct the players' objective function with their direct input. We then test the applicability of our multiple players, multi-issues, stochastic framework to a specific water allocation problem and conduct comparative static analyses to assess sources of bargaining power. Finally, we explore the implications of different attitudes and beliefs over water availability.
Keywords: C61; C71; C78; 330; bargaining; non-cooperative game theory; simulation models; uncertainty; Verhandlungstheorie; Nichtkooperatives Spiel; Simulation; Wasserversorgung; Venetien; Italien